ICT Literacy for Indonesian Workers in Singapore - Mutia Delina; Bambang Iswanto; Lipur Sugiyanta; Faisal Madani; Surano Muhasyah; Muhammad Ilham Fauzi; Ahmad Fauzan (LPPM Universitas Negeri Jakarta, 2021)
Information and communication technology (ICT) has become an essential aspect of modern life. Everybody has to deal with ICT, especially for work. In Asia, ICT skills involve five main aspects: software development, ICT project management, enterprise architecture design, network and system administration, and information system and network security. Every year Indonesia sends workers to Singapore. In contrast, most of those workers are skilled workers for the household which their job responsibilities are taking care of the house, babysitting, taking care of the elderly and drivers. However, some of them have ICT skills, and some others do not have them. Therefore, Universitas Negeri Jakarta conducted a webinar on